Mapping Research Trends on Open Innovation Strategies in Multinational Collaboration - Loso Judijanto; Nofirman Nofirman; Syamsulbahri Syamsulbahri; Rusdianto Rusdianto; Jayadi Jayadi; Kurniawan Kurniawan (The Eastasouth Management and Business, 2025)
This bibliometric analysis study explores the evolving landscape of open innovation strategies within multinational collaborations over the last two decades. Utilizing data extracted from the Scopus database, this research maps out the thematic and collaborative networks to understand how open innovation has been integrated into different research areas and industries. Key themes such as knowledge management, technology transfer, and sustainable development were identified as closely linked to open innovation. The study also highlights significant geographic distributions, pinpointing the United States, China, and several European countries as central nodes in the global research network. These countries not only dominate the field in terms of publications but also in their roles in fostering international academic collaborations. The findings suggest that open innovation is a vibrant and integral part of modern business strategies and research, benefiting significantly from multinational and interdisciplinary collaborations. This study contributes to the literature by providing a comprehensive overview of the field’s evolution, highlighting influential researchers and identifying emerging trends that could guide future research directions.